Non-Orthogonal Multiple Access: The Case of Improper Gaussian Signaling and Imperfect Successive Interference Cancellation - Abu Mahady, Islam; Bedeer, Ebrahim; Ikki, Salama (Frontiers in Communications and Networks, 2022)
This paper studies a two-user downlink non-orthogonal multiple access (NOMA) system that adopts an improper Gaussian signaling (IGS) strategy to compensate for the performance loss due to imperfect successive interference cancellation (SIC). Joint optimization problems are formulated to maximize the overall spectral efficiency and energy efficiency of a two-user NOMA system under minimum user-rate requirements and total power constraints. Sub-optimal solutions of IGS circularity coefficients and power allocation are obtained for the formulated problems. Furthermore, improper constellation diagrams are designed using widely linear transformation with predefined optimized IGS coefficients to study the impact of IGS on throughput and error performance. Simulation results show that the performance of IGS-based NOMA systems, where the IGS strategy is adopted by both users, outperforms that of the proper Gaussian signal (PGS)-based NOMA system under imperfect SIC.